admin

2 months ago

Guest #6877559

2 months ago

L=5+W

P=2(L+W)

38=2(L+W)

divide by 2

19=L+W

sub 5+W for L

19=5+W+W

19=5+2W

minus 5 both sides

14=2W

divid both sides by 2

7=W

L=5+W

L=5+7

L=12

area=LW

are=12 times 7

area=84 yd²

P=2(L+W)

38=2(L+W)

divide by 2

19=L+W

sub 5+W for L

19=5+W+W

19=5+2W

minus 5 both sides

14=2W

divid both sides by 2

7=W

L=5+W

L=5+7

L=12

area=LW

are=12 times 7

area=84 yd²

Question

Which expression is equivalent to the given expression? 8(3/4a)−8
1. 3/4a
2. 6a
3. 8(3/4a - 1)
4. 3/4a -1

Solution 1

**Answer:**

The correct option is 3.

**Step-by-step explanation:**

The given expression is

The factors of each term are

The common factor is 8.

Take out the common factor from the given expression.

**Therefore option 3 is correct.**

Solution 2

8(3/4a)−8 = 8(3/4a - 1)

answer 3. 8(3/4a - 1)

answer 3. 8(3/4a - 1)

Question

PLZ HLP ASAP!!! A park is 2000 hectares in area. If the park is square, what would be the length of each side in kilometers, to the nearest tenth of a kilometer? (1 square kilometer = 100 hectares)

Solution 1

(1 square kilometer = 100 hectares). hope this helps you out but idk the answers so only thing i can do is give u help but hope it helps you :)

Question

Find all the zeros. SHOW ALL WORK!
5x^3 – 5x = 0
Thank you for your help :)

Solution 1

Factor

remember

if xy=0, assume that x and y=0

also

difference of 2 perfect squares

a²-b²=(a-b)(a+b)

so

5x³-5x=0

factor out 5x

5x(x²-1)=0

5x(x²-1²)=0

factor perefect square

5x(x-1)(x+1)=0

set each to zero

5x=0

x=0

x-1=0

x=1

x+1=0

x=-1

x=-1 or 0 or 1

remember

if xy=0, assume that x and y=0

also

difference of 2 perfect squares

a²-b²=(a-b)(a+b)

so

5x³-5x=0

factor out 5x

5x(x²-1)=0

5x(x²-1²)=0

factor perefect square

5x(x-1)(x+1)=0

set each to zero

5x=0

x=0

x-1=0

x=1

x+1=0

x=-1

x=-1 or 0 or 1

Question

Sn: 1 ∙ 2 + 2 ∙ 3 + 3 ∙ 4 + . . . + n(n + 1) = [n(n + 1)(n + 2)]/3

Solution 1

Steps to inductive

1. show it's true for n=1

2. replace n with k

3. replace k with k+1 and show it is true statement

4. state that it's true

1. show it's true for n=1

1(1+1)=[1(1+1)(1+2)]/3

1(2)=[(2)(3)]/3

2=6/3

2=2

true

2. assume it's true for n=k

1*2+2*3+3*4+...+k(k+1)=[k(k+1)(k+2)]/3

3. show it's true for replaceing k with k+1

1*2+2*3+3*4+...+k(k+1)+(k+1)((k+1)+1)=[(k+1)((k+1)+1)((k+1)+2)]/3

remember from before that 1*2+2*3+3*4+...+k(k+1)=[k(k+1)(k+2)]/3

[k(k+1)(k+2)]/3+(k+1)(k+2)=[(k+1)(k+2)(k+3)]/3

use algebra to show this is true (get it to k=k or something like that)

here's the fun part

deal with left side to get to like right side

[k(k+1)(k+2)]/3+(k+1)(k+2)

make over 3, so muliptlu 2nd thing by 3/3

[k(k+1)(k+2)]/3+((k+1)(k+2)3)/3

[k(k+1)(k+2)+3(k+1)(k+3)]/3

we can undistribute the (k+1)(k+2) part

[(k+1)(k+2)(k+3)]/3

now remember the right side?

[(k+1)(k+2)(k+3)]/3=[(k+1)(k+2)(k+3)]/3

tada

true

4. state it

therefor 1 ∙ 2 + 2 ∙ 3 + 3 ∙ 4 + . . . + n(n + 1) = [n(n + 1)(n + 2)]/3 is true for all real numbers

1. show it's true for n=1

2. replace n with k

3. replace k with k+1 and show it is true statement

4. state that it's true

1. show it's true for n=1

1(1+1)=[1(1+1)(1+2)]/3

1(2)=[(2)(3)]/3

2=6/3

2=2

true

2. assume it's true for n=k

1*2+2*3+3*4+...+k(k+1)=[k(k+1)(k+2)]/3

3. show it's true for replaceing k with k+1

1*2+2*3+3*4+...+k(k+1)+(k+1)((k+1)+1)=[(k+1)((k+1)+1)((k+1)+2)]/3

remember from before that 1*2+2*3+3*4+...+k(k+1)=[k(k+1)(k+2)]/3

[k(k+1)(k+2)]/3+(k+1)(k+2)=[(k+1)(k+2)(k+3)]/3

use algebra to show this is true (get it to k=k or something like that)

here's the fun part

deal with left side to get to like right side

[k(k+1)(k+2)]/3+(k+1)(k+2)

make over 3, so muliptlu 2nd thing by 3/3

[k(k+1)(k+2)]/3+((k+1)(k+2)3)/3

[k(k+1)(k+2)+3(k+1)(k+3)]/3

we can undistribute the (k+1)(k+2) part

[(k+1)(k+2)(k+3)]/3

now remember the right side?

[(k+1)(k+2)(k+3)]/3=[(k+1)(k+2)(k+3)]/3

tada

true

4. state it

therefor 1 ∙ 2 + 2 ∙ 3 + 3 ∙ 4 + . . . + n(n + 1) = [n(n + 1)(n + 2)]/3 is true for all real numbers

Question

Which expression is equivalent to the given expression? 8(3/4a)−8
1. 3/4a
2. 6a
3. 8(3/4a - 1)
4. 3/4a -1

Solution 1

**Answer:**

**Step-by-step explanation:**

8 (3/4a) - 8

The above expression can be written as:

Since 8 is a common factor here which is multiple of 3/4a as well as 1 therefore taking 8 as a common factor from whole equation,

Therefore option (3) is the correct answer.

Solution 2

The answer is 3 cause we can factor 8 from the whole equasion .

that means to take 8 out of every given data so

since we have 8 multiple 3/4a we can have an 8 and we also have -8 so we can divide it to 8 and take 8 out of it which leads us to 8(3/4a-1)

that means to take 8 out of every given data so

since we have 8 multiple 3/4a we can have an 8 and we also have -8 so we can divide it to 8 and take 8 out of it which leads us to 8(3/4a-1)

Question

When a nonzero rational and an irrational number are multiplied, is the product rational or irrational?

Solution 1

The sum of a rational number and an irrational number is irrational.

Question

Harvey is 3 times as old as Jane. The sum of their ages is 48 years. Find the age of each. Jane is a0 years old. Harvey is a1 years old.

Solution 1

Let jane = j

Harvey = 3*j = 3j

Sum = 48 years

j + 3j = 48

4j = 48

j = 48/4

j = 12

Jane, j =**12 years old**

Harvey, 3j = 3*12 =**36 years old**

Hope this helped.

Harvey = 3*j = 3j

Sum = 48 years

j + 3j = 48

4j = 48

j = 48/4

j = 12

Jane, j =

Harvey, 3j = 3*12 =

Solution 2

Harvey is 36, jane is 12

Question

When calculating the effective rate of a loan, which statement or statements must be true if n is greater than 1? I. The length of the loan is greater than a single year.
II. The effective rate will exceed the nominal rate.
III. The interest will be compounded monthly.

Solution 1

Thank you for posting your question here at brainly. I hope the answer will help you. Feel free to ask more questions.

When calculating the effective rate of a loan, the statement or statements must be true if n is greater than 1 is The length of the loan is greater than a single year.

When calculating the effective rate of a loan, the statement or statements must be true if n is greater than 1 is The length of the loan is greater than a single year.

Solution 2

**Answer: A**

**Step-by-step explanation:**

its a

Question

All equilateral triangles are also isosceles triangles.
TRUE OR FALSE?

Solution 1

false kljfoidjfdiojfoidjfoijfoidjfodijfoidjf

Solution 2

**Answer:**

I think it's true but not 100% sure :)

**Step-by-step explanation:**

Question

Which expression is equivalent to the given expression? −(2n−6)
1. −2(n−3)
2. −2(n−6)
3. 2n−62
4. 2n + 6

Solution 1

−(2n−6)

= -2n + 6

= -2(n - 3)

answer is 1. −2(n−3)

= -2n + 6

= -2(n - 3)

answer is 1. −2(n−3)

Mathematics
2647929

History
842281

English
748681

Biology
586256

Social Studies
406852

Chemistry
368373

Business
348603

Physics
324927

Health
199835

Spanish
130075

Geography
112100

Computers and Technology
106146

Arts
77164

Advanced Placement (AP)
23675

World Languages
23213

French
22589

Engineering
19607

Law
17108

Medicine
13966

SAT
10987

German
3389

High School
3423409

Middle School
2092250

College
1518097